Representación de la nostalgia en las crónicas sobre migración escritas por María Fernanda Ampuero y publicadas en las compilaciones Permiso de Residencia y Me Fui a Volver - Vera Ordoñez, Mercy Anabel (2023)
In the present work, it was proposed to analyze the ways in which nostalgia is represented in María Fernanda Ampuero's chronicles on migration published in the compilations Permiso de Residencia and Me Fui a Volver through the identification of situations, practices and objects, and the characterization of the experiences of nostalgia narrated in the chronicles that make up the corpus of this research. The study presents a qualitative approach of descriptive character, the technique used is thematic analysis whose instrument corresponds to a table of registration and systematization of extracted quotations. The corpus used in the research corresponds to 17 chronicles selected from the compilations Permiso de Residencia (2013) and Me Fui a Volver (2014), which relate the experiences of migrants in their journey from Ecuador to the country of destination, mostly Spain, as well as their process of adaptation to the new place of residence. Among the results we can highlight that the situations related to nostalgia are: caring for others, incomplete regrouping, work situations in the country of residence and the type of migration and separation, as well as nostalgia is presented through the relationship of migrants with objects such as: photographs, gastronomic and traditions and, finally, the process of adaptation of migrants makes them develop practices such as gastronomic, entertainment, religious, telephone calls and viewing photographs. It is evident that migration chronicles represent different types of nostalgia experiences, and that they are classified into simple nostalgia determined by longing, yearning or affection for a past life moment, reflective nostalgia, the person makes a comparison and replication of events or the loss of something or someone, and interpretive nostalgia which is based on the reproduction of activities associated with culture, food, dances, music, among others.